2003
DOI: 10.1093/humrep/deg461
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endometrial thickness on IVF/ICSI outcome

Abstract: Increased endometrial thickness is associated with higher pregnancy rates. However, neither attainment of pregnancy nor pregnancy outcome was predicted by endometrial thickness alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
165
2
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(193 citation statements)
references
References 17 publications
20
165
2
6
Order By: Relevance
“…Similar findings were reported by Noyes et al [3]. Kovacs et al [4] also reported that increased endometrial thickness was significantly associated with higher pregnancy rates. In our study, no pregnancy was reported when endometrial thickness was less than 7 mm.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were reported by Noyes et al [3]. Kovacs et al [4] also reported that increased endometrial thickness was significantly associated with higher pregnancy rates. In our study, no pregnancy was reported when endometrial thickness was less than 7 mm.…”
Section: Discussionsupporting
confidence: 87%
“…A number of studies have indicated a higher pregnancy rate at a partic- ular endometrial thickness (29)(30)(31)(32)(33), while alternative studies indicated no significant correlation between endometrial thickness and pregnancy rates in IVF/ICSI patients (34)(35)(36)(37)(38)(39). The present study indicated that clinical pregnancy rates following embryo transfer are positively correlated with endometrial thickness, which is consistent with previous studies (39)(40)(41).…”
Section: Discussionsupporting
confidence: 88%
“…A number of studies have evaluated the association between endometrial thickness and pregnancy rates in patients undergoing assisted reproductive technology; however, the results remain controversial (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). A number of studies have indicated a higher pregnancy rate at a partic- ular endometrial thickness (29)(30)(31)(32)(33), while alternative studies indicated no significant correlation between endometrial thickness and pregnancy rates in IVF/ICSI patients (34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial thickness has been reported to be one of the most important factors for success in ART. Zhang et al [12] reported a significant difference in the pregnancy rate in patients with an endometrial thickness above and below 9 mm, whereas Kovacs et al [13] and Richter et al [14] showed a gradual increase in the implantation rate with increasing endometrial thickness. In the present study, none of the patients whose endometrial thickness was <7 mm achieved a live-birth (data not shown).…”
Section: Discussionmentioning
confidence: 99%